Sexting and Sexual Satisfaction on Young Adults in Romantic Relationship - Oriza, Imelda Ika Dian; Hanipraja, Magdalena Anastasia (Psychological Research on Urban Society, 2020)
The integration of technology into everyday life contributes to the urgency to study virtual activities within the context of a romantic relationship, one of them being sexting or the exchange of sensual messages through communication technology. Sexting, until recently, had been looked upon as risky sexual behavior. Researchers, however, have come to view sexting as a positive activity in romantic relationships, especially in regards to sexual satisfaction. Sexual satisfaction may be enhanced by sexting as it can function as a means of sexual communication and activity. This research aims to investigate the relationship between sexting and sexual satisfaction, especially with sexting as the predictor of sexual satisfaction. Regression analysis is used to test the hypothesis, and the result shows that sexting significantly predicted sexual satisfaction (F(1,70) = 8,602, p = 0,005, < 0,01) with the determinant coefficient of 0,109, interpreable as 10,9% variance of sexual satisfaction explained by sexting.